2020
DOI: 10.1093/rheumatology/keaa737
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular mortality and cardiovascular event rates in patients with inflammatory rheumatic diseases in the CARdiovascular in rheuMAtology (CARMA) prospective study—results at 5 years of follow-up

Abstract: Objectives To determine cardiovascular (CV) mortality and incidence of the first CV event (CVE) in patients with chronic inflammatory rheumatic diseases (CIRD) after 5 years of follow-up. Methods This is an analysis of the CARdiovascular in rheMAatology (CARMA) study after 5 years of follow-up. It includes patients with RA (n = 775), AS (n = 738) and PsA (n = 721), and individuals without CIRD (n = 677) attending outpatient r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…At that time, the CARMA project member speculated on the protective effect of the biologic therapy administered to a high number of patients, due to the favorable effect of biologics on the insulin resistance, lipid composition, and other beneficial metabolic effects mediated by these agents, as well as the effect on reducing inflammation. Likewise, the greater knowledge of the EULAR recommendation for the management of traditional CV risk factors among the members of the CARMA project may also have explained these favorable results ( 31 ). The discrepancy supports the gap in proper stratification and treatment of the patients with RA in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…At that time, the CARMA project member speculated on the protective effect of the biologic therapy administered to a high number of patients, due to the favorable effect of biologics on the insulin resistance, lipid composition, and other beneficial metabolic effects mediated by these agents, as well as the effect on reducing inflammation. Likewise, the greater knowledge of the EULAR recommendation for the management of traditional CV risk factors among the members of the CARMA project may also have explained these favorable results ( 31 ). The discrepancy supports the gap in proper stratification and treatment of the patients with RA in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A low level of education and general comorbidities (including CV diseases) were identified as predictors of death ( 16 ). In a Spanish study analyzing CV mortality and CV events at 5 years in different IRD, AS was found to have the highest risk of a first CV event [HR: 4.6 (1.32–15.99)], but without increased CV deaths ( 17 ). Finally, a recent meta-analysis concluded that CV mortality in AS was increased, with a relative risk (RR) of 1.46 [1.15–1.86] ( 18 ).…”
Section: Mortality In Axspamentioning
confidence: 99%
“…However, the CARdiovascular in rheuMAtology (CARMA) project in Spanish patients revealed a lower rate of cardiovascular events and cardiovascular deaths in patients with chronic inflammatory rheumatic diseases, including RA. 29 Different genetic components and biologics usage percentage in the two groups might be parts of the possible explanations. López-Mejías et al 30 summarized the genetic factors associated with the risk of cardiovascular disease in RA patients, including the HLA class II histocompatibility antigen, DRB1 beta chain ( HLA-DRB1 ) gene, especially the HLA-DRB1*04 shared epitope (SE) alleles, and some polymorphisms inside and outside the HLA region such as the TNFA rs1800629 polymorphism (located at TNFA promoter), the C -C chemokine receptor type 5 ( CCR5)Δ32 rs333 polymorphism (a 32-basepairs deletion), and the methylenetetrahydrofolate reductase (MTHFR) rs1801131 polymorphism.…”
Section: Discussionmentioning
confidence: 99%